Dynamics Modeling and Experimental Analysis of Omnidirectional Mobile Manipulator - Hong Zhang; Yumin Zeng; Tongde Wang (Jixie chuandong)
In order to improve the control precision of the omnidirectional mobile manipulator, its kinematics model and dynamics model are established. Firstly，the kinematics model of the omnidirectional mobile platform is established according to the characteristics of the Mecanum wheel. The kinematics equation of the 5-DOF manipulator is derived according to the DH rule， and the unified kinematics equation is derived by combining the basis coordinate of manipulator with the centroid of mobile platform. Then，based on the kinematics model，by using the second type of Lagrangian equation，considering the coupling relationship between the mobile platform and the manipulator，considering the energy dissipation problem，the unified dynamics model of the omnidirectional mobile manipulator is established. Finally，the experimental prototype is built according to the design，and two different torque indirect measurement methods are used. The real-time torque is measured in different motion modes of the prototype，and compared with the calculated torque value calculated by the dynamics equation. The result shows that the built dynamics model is correct and reliable，which provides a theoretical basis for future motion control.